Exploring Factors Contributing to Stunting in Children Under 5 Years: Systematic Review - Diva' Noeriza Aredya Adlinsyah; Mohammad Zen Rahfiludin; Sri Winarni (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting is representation of inhibited growth as a result of prolonged insufficient nutrient intake. Around 45% of deaths among children under 5 years of age linked to undernutrition. The purpose of this systematic review is to analyze the factors that play a role in causing stunting in children under the age of 5, by conducting recent research and examining variables as causes of stunting through a literature review of published journal studies. This research is a systematic review based on articles published from 2014 to 2023. The research sample consists of published articles in Scopus, PubMed, and ScienceDirect, and 12 articles that meet the inclusion criteria were obtained. Stunting is caused by several factors, including: Low Birth Weight Child, age child, gender child, age mother, mother education, media exposure, household wealth, family size, residential area, sorce of drinking water, birthing location, and access to sanitation facilities. Currently, stunting remains a health issue in early childhood that requires the best healthcare services. Addressing stunting requires the best health services and serious attention to these factors